2012
DOI: 10.1161/strokeaha.111.636035
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids and Delayed Cerebral Ischemia After Subarachnoid Hemorrhage

Abstract: Background and purpose To understand factors related to increases in serum free fatty acid levels (FFA) and association with delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH). Methods Serial measurement of systemic oxygen consumption (VO2) by indirect calorimetry (IDC) and FFA levels by liquid chromatography/mass spectrometry in the first 14 days after ictus in 50 consecutive SAH patients. Multivariable GEE models identified associations with FFA levels in the first 14 days after SAH and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In previous studies, we and others have identified the importance of assessing free fatty acid metabolism and supplementation on the occurrence of DCI. 18,42,43 Protein energy malnutrition identified in this study may be another target for intervention with amino acid supplementation. Prospective studies assessing the impact of specific amino acids and inflammation on outcome are needed to determine whether immunomodulation with nutritional supplementation may provide benefit after SAH.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In previous studies, we and others have identified the importance of assessing free fatty acid metabolism and supplementation on the occurrence of DCI. 18,42,43 Protein energy malnutrition identified in this study may be another target for intervention with amino acid supplementation. Prospective studies assessing the impact of specific amino acids and inflammation on outcome are needed to determine whether immunomodulation with nutritional supplementation may provide benefit after SAH.…”
mentioning
confidence: 87%
“…Our methodology for IDC has been described previously. 17,18 In mechanically ventilated subjects, the IDC circuit system was connected to the oxygen delivery and exhaust systems of the ventilator, whereas in non-mechanically ventilated subjects, the IDC circuit was connected to an airtight canopy that covered the subject's head and neck and delivered a measured constant flow of air (21% O 2 ).…”
mentioning
confidence: 99%
“…Food rich in flavanols, particularly cocoa, may improve endothelial function in general [299]. Food rich in omega-3 fatty acids improves vascular regulation [300]. We also recommend green tea [301].…”
Section: Therapymentioning
confidence: 99%
“…[ 32 ] Free fatty acids ( n = 6) released during lipolysis of TG induce lipid peroxidative injury. [ 2 ] Excess fat reserve or metabolic syndrome associated with elevated TG levels may also cause release of pro-inflammatory adipokines and/or endothelial dysfunction. [ 27 ] Higher skin-fold measures of adiposity have been noted to be significantly associated with vasospasm.…”
Section: Discussionmentioning
confidence: 99%